PENGARUH KOMPONEN IKLIM ORGANISASI TERHADAP KETERLIBATAN KERJA KARYAWAN - AMANU, RAIHANA FARRAS; GULO, YUPITER (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
This study aims to analyze and determine the influence of organizational climate components including leadership, employee relations, employee commitment, employee satisfaction, and employee motivation on work engagement. This research uses descriptive and causal approaches and uses a 5-point Likert scale to measure each variable. This study used non-probability sampling technique with saturated sampling method. Data collection was obtained by through questionnaires distributed online through Google Form to 65 respondents. This research method uses the multiple linear analysis method was used as a test tool. The results in this study showed that leadership, employee relations, employee engagement, employee satisfaction and employee motivation affect employee work engagement.